Study on greening cloud computing and electronic communications services and networks - Bilsen, Valentijn,Gröger, Jens,Devriendt, Willem,Liu, Ran,Gaušas, Simonas,Behrens, Felix,Bley, Federico,Carpentier, Marieke,Duchêne, Vincent,Köhler, Andreas R.,Lecocq, Cathy,Legein, Emma,Quack, Dietlinde (Publications Office of the European Union, 2022)
The current rapid digital transformation is characterized by an increase in the generation, use and transmission of data, and IT infrastructure, which in turn leads to an increased energy and resource consumption. Therefore in view of the EU Green Deal and related policy strategies, the digital transformation also requires a green transformation. Therefore the broad objectives of this study are to propose i) policy measures for increasing the energy and resource efficiency of data centres as well as ii) policy options that could be included in a transparency mechanism on the environmental footprint of electronic communications services and networks (ECNs) and criteria for environmental sustainability assessments. A dual research strategy was followed, focussing on data centres and cloud computing on the one hand and ECNs on the other hand. For data centres the study proposes primarily (a combination of) the following policy measures: - Improvements to the Code of Conduct; - Compulsory green public procurement criteria for publicly procured data centres, server rooms and cloud services; and - The set-up of a European Data Centre Registry. Concerning ECNs, the two main propositions are: - The deployment of a energy efficient network infrastructure; - The provision of eco-friendly telecommunications services by ECN operators.
10.2759/116715
Keywords: Graue Literatur; Amtliche Publikation; Cloud Computing; IT-Infrastruktur; Energieeinsparung; Nachhaltigkeit; EU-Staaten; digital transformation; data transmission; cloud computing; computer network; EU strategy; energy consumption; EU environmental policy; energy efficiency; national implementing measure; ecological footprint; sustainable development; code of conduct; green public procurement; telecommunications; report